2015
DOI: 10.1103/physrevlett.114.227201
|View full text |Cite
|
Sign up to set email alerts
|

Spin Pumping in Electrodynamically Coupled Magnon-Photon Systems

Abstract: We use electrical detection, in combination with microwave transmission, to investigate both resonant and non-resonant magnon-photon coupling at room temperature. Spin pumping in a dynamically coupled magnon-photon system is found to be distinctly different from previous experiments. Characteristic coupling features such as modes anti-crossing, line width evolution, peculiar line shape, and resonance broadening are systematically measured and consistently analyzed by a theoretical model set on the foundation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
399
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 440 publications
(423 citation statements)
references
References 27 publications
(58 reference statements)
10
399
3
3
Order By: Relevance
“…In light of this principle, a cavity magnon polariton (CMP) has been recently studied in a coupled magnon-cavity photon system 2 , where the general feature of the CMP is described in a concise classical model 2 which accurately highlights the key physics of phase correlation between the cavity and magetization resonances. This general CMP model can be used to quantitatively analyze the characteristic features of magnon-photon coupling experiments recently performed by many different groups [2][3][4][5][6][7][8][9][10] , in which a low damping bulk ferromagnetic insulator is set either on-top of a superconducting co-plannar waveguide or inside a high quality 3D microwave cavity.…”
mentioning
confidence: 99%
“…In light of this principle, a cavity magnon polariton (CMP) has been recently studied in a coupled magnon-cavity photon system 2 , where the general feature of the CMP is described in a concise classical model 2 which accurately highlights the key physics of phase correlation between the cavity and magetization resonances. This general CMP model can be used to quantitatively analyze the characteristic features of magnon-photon coupling experiments recently performed by many different groups [2][3][4][5][6][7][8][9][10] , in which a low damping bulk ferromagnetic insulator is set either on-top of a superconducting co-plannar waveguide or inside a high quality 3D microwave cavity.…”
mentioning
confidence: 99%
“…Recently, strong coupling between a microwave cavity mode and ferromagnetic resonance (FMR) has been realized at room temperature [6][7][8][9][10][11][12][13][14][15][16][17] . Exchange interactions lock the high density of spins in YIG into a macro-spin state, leading to strong coupling with a cavity mode which can be adjusted using an external magnetic field.…”
mentioning
confidence: 99%
“…The sign reversal of V shows that the measured signal is not produced by a possible thermoelectric effect, induced by the microwave absorption. The strong coupling in the spin pumping signal (predicted by Cao et al 14 ) has been experimentally observed in a YIG(2.6-2.8µm)/Pt system for which the spin sink layer presents a thickness of 5 7 and 10 nm 6,8 . Even though the S21 parameter illustrates in Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Magnon-photon coupling has been investigated in microwave resonators (three-dimensional cavity [1][2][3][4][5][6][7][8][9][10] and planar configuration [11][12][13] ) loaded with a ferrimagnetic insulator such as Yttrium Iron Garnet (YIG, thin film and bulk). More recently, research groups 6-8 have developed an electrical method to detect magnons coupled with photons.…”
Section: Introductionmentioning
confidence: 99%